HIV/AIDS awareness and related health education needs among slum dwellers of Jodhpur city - Joshi, Vibha; Joshi, Nitin Kumar; Bajaj, Komal; Bhardwaj, Pankaj (Indian Journal of Community Health, 2020)
Background: The people living in slums lack the basic civic amenities. Due to deprivation of socioeconomic resources and health care facilities these groups of people are more vulnerable to infectious diseases like HIV/AIDS. Aim& Objective: To assess the knowledge and awareness about HIV/AIDS and to identify related health education needs in urban slums of Jodhpur. Settings and Design: A cross sectional study was conducted during July – Nov 2018 in slums of Jodhpur city. Methods and Material: Two stage cluster sampling strategy was used to collect data from 1200 participants regarding HIV/ AIDS knowledge and awareness to identify health education needs in urban slums. Statistical analysis used: Descriptive statistics, chi-square test and multivariate logistics analysis were used. Results: A total of 1200 participants were surveyed, out of which 48.5 % were males. Among the study population 58% (n=697) has heard about HIV/AIDS and only 17.5% (n=211) have knowledge that the HIV and AIDS are different. Only 17.8% (n=214) have undergone HIV testing. Females were less likely aware about preventive measures of HIV than males (OR=0.09, 95%CI=0.05-0.14, P value<0.05). The younger population (15-45years) were less likely aware about preventive measures for HIV than older population (>45 years). Only 13.9% (n=110) of tobacco consumers and 11.5% (n=78) alcohol consumers have undergone HIV testing. Conclusions: The comprehensive health education program should be designed with focus on different education needs according to age and gender of urban slums.